2012
DOI: 10.1021/ja209829m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Protein Oligomerization: Inhibitor of Functional Amyloids Templates α-Synuclein Fibrillation

Abstract: Small organic molecules that inhibit functional bacterial amyloid fibers, curli, are promising new antibiotics. Here we investigated the mechanism by which the ring-fused 2-pyridone FN075 inhibits fibrillation of the curli protein CsgA. Using a variety of biophysical techniques, we found that FN075 promotes CsgA to form off-pathway, non-amyloidogenic oligomeric species. In light of the generic properties of amyloids, we tested whether FN075 would also affect the fibrillation reaction of human α-synuclein, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 31 publications
9
123
1
1
Order By: Relevance
“…For example, it is reported that in vivo, α-synuclein filaments are 14-16 nm thick [129] and have lengths !1 μM. In contrast, on-pathway (to fibril formation) oligomers are reported to have a Stokes hydrodynamic radius of 7 nm [130,131] and are much shorter. Spherical oligomers, which may be among the toxic species [107], are even smaller at 2-6 nm in diameter, whereas annular oligomers appear under AFM as a dense, remarkably homogeneous population of globular, mildly flattened oligomers with a narrow size distribution (average diameter of 21 AE 3 nm) and with a less dense interior or a pore-like toroid [106,112].…”
Section: α-Synuclein Fibrils: the Pathological Hallmarkmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, it is reported that in vivo, α-synuclein filaments are 14-16 nm thick [129] and have lengths !1 μM. In contrast, on-pathway (to fibril formation) oligomers are reported to have a Stokes hydrodynamic radius of 7 nm [130,131] and are much shorter. Spherical oligomers, which may be among the toxic species [107], are even smaller at 2-6 nm in diameter, whereas annular oligomers appear under AFM as a dense, remarkably homogeneous population of globular, mildly flattened oligomers with a narrow size distribution (average diameter of 21 AE 3 nm) and with a less dense interior or a pore-like toroid [106,112].…”
Section: α-Synuclein Fibrils: the Pathological Hallmarkmentioning
confidence: 95%
“…Conversely, a particular molecule may have opposing effects on structurally related targets, for example, by promoting off-pathway oligomers of one target but promoting fibrillization of another [131]. Thus, structure-based predictions regarding mechanism of binding and resulting α-synuclein species are difficult.…”
Section: Small Molecules That Target α-Synuclein Aggregationmentioning
confidence: 99%
“…A screen of compounds originally designed to inhibit the elaboration of E. coli P pili yielded a set of small molecules capable of inhibiting amyloid formation of Aβ [99, 100]. These compounds have since been subject to extensive chemical modification and assayed for biological activity against several amyloid substrates including curli [28, 91, 101]. This extensive library of 2-pyridone compounds, or curlicides, exhibit varying degrees of CsgA amyloid inhibition and curli-dependent biofilm inhibition [28, 91, 101].…”
Section: Folding Intermediates Can Be Probed Using Antibodies and mentioning
confidence: 99%
“…Analytical ultracentrifugation (AUC) measurements combined with the H/D exchange [41,42] and fluorescence analyses [43] have shown that amyloid core (residues 40-80) is consistently protected from the solvent in oligomers, and in some oligomer preparations this protection is extended on all N-terminal half of the protein (residues 1-90) [41]. Oligomers with smaller solvent-protected core were shown to be not on the pathway to fibril formation, whereas the oligomers with larger protected core were easily converted to fibrils [41,44].…”
Section: A-synuclein Oligomersmentioning
confidence: 99%